2012
DOI: 10.1143/jjap.51.031202
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Study of Defect Levels in CuInS2 Thin Films Grown by Sulfurization Using Ditertiarybutylsulfide

Abstract: The defect-related photoluminescence (PL) levels of CuInS 2 thin films prepared by sulfurization using ditertiarybutylsulfide [(t-C 4 H 9 ) 2 S: DTBS] have been investigated. The PL spectra exhibit three low-energy peaks at 1.37, 1.34, and 1.24 eV. On the basis of these PL spectra observed at different excitation intensities, the emissions are attributed to donor-acceptor pair transitions. The ionization energies of donors in CuInS 2 thin films are determined to be 125, 150, and 280 meV, which are, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…The equipment used was the same as that described in our previous reports. [23][24][25] The thickness of the resulting Cu-rich, CuInS 2 thin films was measured to be approximately 2.0 m. X-ray diffraction (XRD) analysis revealed that the films were composed of a single phase with chalcopyrite structure, and no additional phases.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The equipment used was the same as that described in our previous reports. [23][24][25] The thickness of the resulting Cu-rich, CuInS 2 thin films was measured to be approximately 2.0 m. X-ray diffraction (XRD) analysis revealed that the films were composed of a single phase with chalcopyrite structure, and no additional phases.…”
Section: Methodsmentioning
confidence: 99%
“…The PL peak P1 is due to DAP emission because the peak shifts to a higher energy as the excitation intensity increases. 24,25) In order to further identify the type of the peak P1 emission, excitation intensity dependence of the emission intensity in low temperature (77 K) is shown in Fig. 2(b).…”
Section: Analysis Of the P1 Peakmentioning
confidence: 99%
See 3 more Smart Citations